MALPRAKTEK YANG DILAKUKAN OLEH DOKTER DI RUMAH SAKIT - Sagung Putri (Jurnal Aktual Justice, 2018)
The research is a research which aims to find out the criminal law policy toward doctors, who do malpractice in hospital, and to know the criminal liability of hospital for doctors who do malpractice in health service, and to see the role of Government Hospital in protecting society from malpractice done by a doctor. By law, hospitals and doctors may be held criminally liable in accordance with the provisions of Article 46 of the Hospital Law, Article 359 of the Criminal Code, and Article 361 of the Criminal Code. Hospital corporations can also be held criminally liable in accordance with the provisions of superior respondent theory, hospital liability, and strict liability. Criminal law policies against malpractice doctors in hospitals may be granted in accordance with elements of the act committed by legal subjects, the existence of errors, the existence of acts committed are unlawful, the perpetrator capable of responsible, and the existence of exceptions to criminal elimination.